A Sequence-Ready BAC Clone Contig of a 2.2-Mb Segment of Human Chromosome 1q24 - Vollrath, Douglas; Jaramillo-Babb, Virna L. (Genome Research, 1999)
Human chromosomal region 1q24 encodes two cloned disease genes and lies within large genetic inclusion intervals for several disease genes that have yet to be identified. We have constructed a single bacterial artificial chromosome (BAC) clone contig that spans over 2 Mb of 1q24 and consists of 78 clones connected by 100 STSs. The average density of mapped STSs is one of the highest described for a multimegabase region of the human genome. The contig was efficiently constructed by generating STSs from clone ends, followed by library walking. Distance information was added by determining the insert sizes of all clones, and expressed sequence tags (ESTs) and genes were incorporated to create a partial transcript map of the region, providing candidate genes for local disease loci. The gene order and content of the region provide insight into ancient duplication events that have occurred on proximal 1q. The stage is now set for further elucidation of this interesting region through large-scale sequencing.[The sequence data described in this paper have been submitted to GenBank under accession nos. G42259–G42312 and G42330–G42335.]